The Baltic - man and nature - Furman, Eeva (Otava Publishing Co. Ltd HelsinkiFI, 1998)
Tells of the geology, living nature and people of the Baltic and their interactions over the ages, including the present. Provides descriptions of the environmental problems afflicting the Baltic Sea and its drainage basin, together with an account of the efforts which are being made to improve its condition.